THE DIVERSITY OF MEDICINAL AND AROMATIC PLANTS ENCOUNTRED IN NATURA 2000 6520 HABITAT FROM GURGHIU MOUNTAINS - Silvia OROIAN; Mihaela SAMARGHITAN; Mariana HIRITIU; Sanda COSARCA; Corneliu TANASE (Journal of Plant Development, 2016)
Researches on medicinal plants used in various human disorders are particularly important and timely, as an alternative to medication. The studied semi-natural mountainous grasslands occur in the Gurghiu mountains. Special interest today worldwide for herbal medicine has led us to study the Gurghiu Mountains medicinal plants used in various diseases. In order to identify the taxa we used classical methods, described in the literature and statistical analyze was also carried out. In the study area 2 plant associations rich in medicinal plants were identified. They belong to 6520 Mountain hay meadows habitat.